Strength, Cuttability, and Workability of Coal - Bilgin, Nuh; Copur, Hanifi; Balci, Cemal; Tumac, Deniz; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
World coal production will increase up to 2040 and world energy consumption will be very much dependent on coal. For a better planning of coal mining operations, it is essential to know the strength, cuttability and workability of coal, which are interrelated. The main objective of the book is to combine the research studies and compile the book oriented to the coal industry, research students, practicing engineers, and coal mine panning teams. Key Features Covers all the subjects related to coal properties, mining and excavation in one book Presents a summary of physical and mechanical properties of coal belonging to a wide range of countries Includes typical examples of using physical and mechanical of coal in mine planning and in its industrial applications Explains use of cuttability characteristics of coal Describes planning of coal production using ploughs, shearers and surface miners
1. Introduction -- 2. Coal in the World, Reserves, Productions, the Use of Coal in -- Industry and Prices -- 3. Coal in Turkey, Reserves, Properties, and Characteristics -- 4. Coal Petrology, Classification, Hardness, and Breakage -- Characteristics of Lithotypes -- 5. Physical and Mechanical Characteristics of Coal -- 6. Schmidt Hammer Hardness, In-Situ Strength of Coal, Cleats -- 7. Cutting of Coal, Coal Cutting Mechanics, Laboratory Coal -- Cutting Experiments -- 8. Coal Properties Effecting Coal Cuttability -- 9. Workability of Coal, Drilling and Digging/Breaking the Coal -- 10. Effect of Coal Cutting Methods on Final Properties of the -- Produced Coal that would be Relevant to Later Coal Upgrading -- and Utilization -- 11. Mechanized Underground Coal Exploitation Methods: -- Longwall, Room and Pillar and Shortwall -- 12. Cutting Coal with Plows, a Trend toward Mining Thinner -- Coal Seams -- 13. Cutting Coal with Shearers, Some Application Examples -- 14. Cuttability Criteria for the Use of Continuous Surface Miners -- and Worldwide Applications in Surface Coal Mining.
Includes bibliographical references and index.
Also available in print format.
Keywords: Coal -- Analysis; Coal mines and mining; Coal-mining machinery; TECHNOLOGY & ENGINEERING / Civil / Soil & Rock; TECHNOLOGY & ENGINEERING / Material Science; Electronic books